Social Partnership Approach for Effective Social Worker Education; International Review of Management and Marketing; Vol. 6, iss. 2S - Eremeeva T. S. Tatjyana Sergeevna; Leyfa A. V. Andrey Vasiljevich; Shchepkina N. K. Neile Kayumovna; Shcheka N. Yu. Nataljya Yurjevna; Palyanov M. P. Mikhail Pavlovich; Morozova M. V. Marina Vyacheslavovna; Rudneva E. L. Elena Leonidovna; Gzhemskaya N. K. (2016, 2016)
Title screen